Public Opinion Supervision: A Case Study of Media Freedom in China - Cheung, Anne S. Y. (Columbia Journal of Asian Law, 2007)
Since the late 1970s, the People’s Republic of China has experienced a rise of investigative journalism along with economic liberalization. Scholars contend that with the introduction of capitalism and the consequent relaxation of media control, a degree of real press freedom has crept into China’s society.4 In particular, scholars highlight a unique phenomenon known as yulunjiandu, or “public opinion supervision,” where citizen awareness of an issue is mobilized to act as a check against the state, to influence court decisions, or to push for legislative or policy reforms. The media plays a critical role in this process. Many perceive the media as a positive force in China through which the public can be heard, and some equate public opinion supervision to a form of media monitoring, where the media serves as an independent watchdog monitoring the government.